THE RELATIONSHIP BETWEEN COMPENSATION AND BENEFIT, WORK ENVIRONMENT AND ORGANIZATIONAL SUPPORT ON EMPLOYEE LOYALTY IN LEGAL FIRMS IN KLANG VALLEY - Fatin Nabilah Ahmad Azam; Azahari Jamaludin; Ahmad Fauzi Ahmad Zaini; Sheikh Muhamad Hizam Shei (International Journal of Accounting, Finance and Business, 2022)
Employee loyalty plays an important role in the success of the business of legal firms. The success of the business of the legal firms depends largely on customer satisfaction. Therefore, investigating the relationship between compensation and benefit, work environment and organizational support on employee loyalty in legal firms will ensure the growth of the business. However, there has yet to be any research done to investigate this relationship in legal firms in Malaysia. Therefore, the objective of this research is to investigate the relationship between compensation and benefit, work environment and organizational support on employee loyalty. The research seeks to find the relationship between the dependent variable (employee loyalty) and the independent variable (compensation and benefit, work environment and organizational support). The research methodology is a cross-sectional study in the form of a survey where questionnaires in google form will be distributed to the employees of legal firms in Malaysia. This study expects that there is a positive relationship between compensation and benefits, work environment and organizational support on employee loyalty in legal firms in Malaysia.